A benzimidazolyl terpyridine-Fe2+ system and its recognition driven molecular model of a traffic light. Issue 1 (5th December 2018) - Sonkar, Avinash Kumar; Rai, Abhishek; Tripathi, Kamini; Sharma, Pooja; Roesky, H. W.; Drew, Michael G. B.; Mishra, Lallan
Abstract : A benzimidazolyl terpyridine (BIT ) selectively detects Fe 2+, F − and CN − ; its Fe 2+ complex1 detects TNP, F − and CN −, with concomitant color changes from purple to red, yellow and green, respectively, which makes it a molecular model of a traffic light. Abstract : A new benzimidazolyl terpyridyl ligand (BIT ) selectively detects Fe 2+, F − and CN − ions in acetonitrile. The Fe 2+ complex [Fe(H-BIT )2 ]·(ClO4 )4 (1 ) displays the fast and selective detection of 2, 4, 6-trinitrophenol (TNP) with strong binding (log β = 8.51 ± 0.24) and a low limit of detection (1.4 × 10 −7 M) among several nitroaromatics. The color of complex1 changes from purple to red, yellow, and green upon the separate addition of 2, 4, 6-trinitrophenol and tetrabutylammonium salts of fluoride and cyanide, respectively. The overall color changes thus display a model of a traffic light. The structures ofBIT, 1 and [Fe(BIT )2 ]·(TNP)2 (2 ) have been well characterized using spectroscopic techniques and single crystal X-ray crystallography.